Improving coherence between development cooperation and other policies - Guido Ashoff (Deutsches Institut für Entwicklungspolitik (DIE), 2002)
The success of development policy partly depends on the effects of other policies which – intentionally or unintentionally – may support, but also impair, development cooperation efforts. Development policy must therefore bear other policies in mind in order to prevent incoherence and generate synergies as far as possible. There are numerous examples of incoherence. Foreign policy, export and labor market interests have repeatedly eclipsed development policy objectives. The EU's trade, agricultural and fisheries policies have counteracted development cooperation projects and programs in several cases. There is a tense relationship between development and arms export policies. Besides these cases of incoherence about which advocates of development cooperation have complained, four factors have given added weight to the subject of policy coherence: (i) the inclusion of the requirement of coherence with development policy in the Maastricht/Amsterdam Treaty, (ii) increased pressure to improve the efficiency and effectiveness of development cooperation in view of declining budget allocations, (iii) the extended right enjoyed by the Federal Ministry for Economic Cooperation and Development (BMZ) since mid-2000 to examine legislation planned by other government departments for its impact on development and (iv) the Program of Action 2015 adopted by the Federal Government in 2001, which calls for a coherent approach by various policies in order to achieve the internationally agreed goal of halving extreme poverty by 2015.The issue of policy coherence has played a growing role in the development policy debate in Germany in recent years. There have been campaigns and a number of proposals for greater coherence. Since 1998, most of the steps taken (in addition to the Program of Action 2015) to improve coherence have been institutional, and they should be fully exploited. Whether the BMZ requires further areas of responsibility to achieve greater coherence should be considered as and when necessary. In general, however, it is true to say that development policy is not just a matter for the BMZ, but a task for many policies. The BMZ should not therefore take on the tasks of other policies and so overexert itself, but increasingly urge and help other government departments to share responsibility for development policy. To this end, three steps seem important: (i) improvement of the BMZ's analytical competence for closer observation of the impact on development of other policies, (ii) intensive coherence-related dialogue with other government departments and (iii) mobilization of political support for greater coherence.
Keywords: 330